Factors that Influence the Going Concern Opinion (Study on the Financial Sector on the Indonesian Stock Exchange for the Period 2019-2024) - Joice Yusheilla Sirait; Renny Maisyarah (Sean Institute, 2025)
Going concern opinion is a crucial assessment issued by auditors to evaluate a company's ability to sustain its operations in the foreseeable future. This study aims to analyze the factors influencing the issuance of going concern opinions in the financial sector companies listed on the Indonesian Stock Exchange (IDX) for the period 2019-2024. Several financial and non-financial factors are considered, including profitability, liquidity, leverage, company size, audit quality, and macroeconomic conditions. This research employs a quantitative approach, utilizing secondary data from financial reports and audit opinions of companies within the financial sector. The data will be analyzed using logistic regression to determine the significance and influence of each variable on the probability of receiving a going concern opinion. The expected findings will provide insights into the key determinants affecting auditors' going concern assessments. This study is essential for investors, regulators, and company management to understand the financial stability of firms and improve corporate governance practices. Furthermore, the research contributes to the auditing literature by examining the role of economic fluctuations and audit quality in shaping going concern opinions.